2009
DOI: 10.1021/jf902054x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phenolic Compounds in Six Norwegian Plum Cultivars (Prunus domestica L.)

Abstract: Six European plum cultivars ( Prunus domestica L.) grown in Norway have been studied with respect to phenolic composition. Neochlorogenic acid was found to be the most important phenolic acid in all cultivars. Together with other phenolic acids, this compound varied significantly in amount among the cultivars. Cyanidin 3-rutinoside was found to account for >60% of the total anthocyanin content. Minor amounts of flavonols (rutin and quercetin 3-glucoside) were detected in all cultivars. Total antioxidant capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
59
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 18 publications
15
59
4
Order By: Relevance
“…The plum fruit is a good source of vitamins, minerals, fiber and enzymes that are good for the digestive system and positively associated with nutrient intake, improves anthropometric measurements; the prune is a useful antistresser (Hiramoto, 2008) and reduces risk of hypertension (Beals and Fulgoni, 2005;Ahmed et al, 2010a). Besides various sugars, acids, pectins, tannins and enzymes, European plum fruits also contain several important secondary metabolites such as flavonoids and phenolic acids (Tomas-Barberan et al, 2001;Gil et al, 2002;Walkowiak-Tomczak et al, 2008;Slimestad et al, 2009), with a strong antioxidant capacity (Kahkonen et al, 1999;Nakatani et al, 2000;Vinson et al, 2001;Kayano et al, 2002Kayano et al, , 2003Kayano et al, , 2004Kikuzaki et al, 2004;Kimura et al, 2008;Rop et al, 2009;Dhingra et al, 2014). Ascorbic acid is another antioxidant present in plum fruit, essential for higher primates and a small number of other species (Gil et al, 2002).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…The plum fruit is a good source of vitamins, minerals, fiber and enzymes that are good for the digestive system and positively associated with nutrient intake, improves anthropometric measurements; the prune is a useful antistresser (Hiramoto, 2008) and reduces risk of hypertension (Beals and Fulgoni, 2005;Ahmed et al, 2010a). Besides various sugars, acids, pectins, tannins and enzymes, European plum fruits also contain several important secondary metabolites such as flavonoids and phenolic acids (Tomas-Barberan et al, 2001;Gil et al, 2002;Walkowiak-Tomczak et al, 2008;Slimestad et al, 2009), with a strong antioxidant capacity (Kahkonen et al, 1999;Nakatani et al, 2000;Vinson et al, 2001;Kayano et al, 2002Kayano et al, , 2003Kayano et al, , 2004Kikuzaki et al, 2004;Kimura et al, 2008;Rop et al, 2009;Dhingra et al, 2014). Ascorbic acid is another antioxidant present in plum fruit, essential for higher primates and a small number of other species (Gil et al, 2002).…”
Section: In Sarpagandha (Rauvolfia Serpentina)mentioning
confidence: 99%
“…give fruits both desirable qualities like color and antioxidant properties and undesirable qualities like astringency and bitterness [7]. Slimestad et al [8] reported that there is a correlation between taste (astringency, bitterness) and content of phenolic compounds which have an important role in the natural defense mechanisms and health benefits of fruits. Moreover, Koh et al [9] reported that flavonoids are particularly interesting as they are potent in vitro antioxidants and are thought to play key roles in many of the processes underlying vascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular masses of procyanidin C1 and quercetin 3-glucoside are 867 and 465, respectively. Prune contains procyanidins, quercetin 3-rutinoside and quercetin 3-glucoside (Nunes et al, 2008;Slimestad et al, 2009). Therefore, the anti-allergic effect of prune extract observed in this study may be partly attributable to polyphenols, such as procyanidins, quercetin 3-rutinoside and quercetin 3-glucoside.…”
Section: Discussionmentioning
confidence: 66%